Analysis of Parking Needs and Arrangements in the Pulau Datok Beach Tourism Area in Sukadana - Alqadri, Istiqomah; Kadarini, S. Nurlaily; Azwansyah, Heri (Jurnal Teknik Sipil, 2025)
Pantai Pulau Datok in Sukadana is one of the region"™s leading tourist destinations, experiencing a steady increase in visitor numbers each year. One of the emerging challenges alongside the rise in tourism activity is the provision of adequate parking facilities. This study aims to analyze parking user characteristics, assess parking demand, and design an optimal parking layout for the area. Primary data were collected through direct surveys of parking users and vehicle entry-exit observations, while secondary data were obtained from relevant agencies. The analysis revealed that peak vehicle accumulation occurred between 15.30 and 18.00, with the dominant parking duration ranging from 30 to 90 minutes. The parking index at some points approached maximum capacity, particularly for four-wheeled vehicles in certain areas. Although the current parking facilities can still accommodate the existing demand, more efficient management and strategic planning for facility expansion are essential to anticipate future increases in tourist visits. Well-organized parking arrangements will enhance visitor comfort and ensure smooth traffic flow within the tourism area.